ANALISIS PENGGUNAAN KOSAKATA SERAPAN DALAM BUKU TEKS BAHASA INDONESIA KELAS VII - Nurun Nisa Bahar; Muhammad Saleh (Universitas Negeri Makassar, 2022)
Analysis of the Use of Absorbed Vocabulary in Indonesian Language Textbook Class VII. This study aims to identify the form of vocabulary and types of absorption vocabulary used in textbooks. The type of research used is qualitative research by describing qualitative descriptive data. The data source of this research is Indonesian Class VII Textbook. Data collection techniques were carried out using reading techniques, note-taking techniques and inventory. The research instrument consisted of the main instrument, namely the researcher and the observation guide table. The results showed that absorption vocabulary in Indonesian textbooks for grade VII, based on absorption vocabulary in the form of adoption, adaptation and hybridization, types of absorption vocabulary were categorized as nouns, adjectives and verbs, there were several findings of absorption vocabulary from foreign and regional languages in Indonesia. Indonesian textbook for class VII. The use of vocabulary and regions tends to be more positioned as objects and in sentences in Indonesian class VII textbooks.